Smart cities: a survey - Alkandari, Abdulrahman; Alnasheet, Meshal; Alshaikhli, Imad Fakhri Taha (Design for Scientific Renaissance, 2012)
A smart city is one that uses a smart system characterized by the interaction between infrastructure, capital, behaviors and cultures, achieved through their integration. From our survey of the smart city concept by reading recent papers in this field, we found no uniform concept of the smart city; some papers discussed it as a general case study, while others dealt with specific parts. This paper is a survey of a number of articles , which we divided into two categories:1-General case study, which covers the topic of smart city in a general framework, and 2-Specific case study, which covers the topic of the smart city from a specific detailed application, such as Traffic Management System, Smart Grid, Wireless Technology,…etc. The results of our research show that the information of communication technology (ICT) covers all areas on smart cities such as government facilities, buildings, traffic, electricity, health, water, and transport. Until now there is no unique definition for smart cities, most of researcher define the smart city form their needs or prospective.